Inventarisasi Tanaman Buah Di Kawasan Taman Buah Kebun Raya Liwa - Chrisnawati, Lili; Putri, Ayu Sasqia; Haryanto, Haryanto (Universitas Muhammadiyah Surakarta, 2021)
The Liwa Botanical Garden is one of the new botanical gardens in the Southern Sumatra. Data accuracy is needed in supporting the function of the Liwa Botanical Garden as an ex-situ conservation center. This study aims to obtain data on the diversity of fruit trees in the Liwa Botanical Garden. The inventory results show there are 12 tribes and 15 species of fruit trees, with a total of 572 specimens. The predominant genus is Myrtaceae (46%) and the species most commonly found is Psidium guava L. (25%). Kebun Raya Liwa adalah salah satu kebun raya baru di kawasan Sumatera Bagian Selatan. Akurasi data diperlukan dalam menunjang fungsi Kebun Raya Liwa sebagai pusat konservasi ex-situ. Studi ini bertujuan untuk memperoleh data keanekaragaman tanaman buah di kawasan taman buah Kebun Raya Liwa. Hasil inventarisasi menunjukkan terdapat 12 suku dan 15 jenis tanaman buah, dengan total keseluruhan mencapai 572 spesimen. Suku yang mendominasi adalah Myrtaceae (46%) dan jenis yang banyak ditemukan adalah Psidium gujava L. (25%).